The case for using the infraorder Coccomorpha above the superfamily Coccoidea for the scale insects (Hemiptera: Sternorrhyncha) - Williams, Douglas J.; Hodgson, Chris J. (Zootaxa, 2014)
The order Hemiptera was formerly divided into two suborders, Heteroptera and Homoptera. The suborder Homoptera was also divided into two convenient groups, the Auchenorrhyncha and the Sternorrhyncha, the latter comprising the superfamilies Aphidoidea, Psylloidea, and Aleyrodoidea, plus the scale insects in the superfamily Coccoidea. Until about the mid-20th century, most workers on scale insects were content to place the scale insects in the family Coccidae but, with the ever-increasing number of subfamilies being raised to family rank, the superfamily rank Coccoidea came into general use. There are now 49 families presently recognised in the scale insects (Ben-Dov et al., 2014) including families based on fossils. In a recent publication by Kozár et al. (2013), family-group names for two families were resurrected and a new name for a new family was discussed, increasing the number of possible family-group names to 52.